Elicitors of the salicylic acid pathway reduce incidence of bacterial canker of kiwifruit caused by Pseudomonas syringae pv. actinidae. (29th August 2014) - Cellini, A.; Fiorentini, L.; Buriani, G.; Yu, J.; Donati, I.; Cornish, D.A.; Novak, B.; Costa, G.; Vanneste, J.L.; Spinelli, F.
Abstract Some strains of Pseudomonas syringae pv. actinidiae (Psa), the causal agent of bacterial canker of kiwifruit, produce plant hormones and toxins which alter the plant hormonal balance and result in the suppression of the salicylic acid (SA)‐dependent plant defences. To determine whether Psa could be affected by stimulation of the SA pathway, Actinidia deliciosa and A. chinensis were treated with compounds which interfere with this pathway, then inoculated with Psa. On A. deliciosa, compounds which stimulate the SA pathway [SA, or its synthetic analogue, acibenzolar‐S‐methyl (ASM)] or close stomata (ABA) resulted in disease reduction, while methyl‐jasmonate (MJA) or ethylene increased disease development. On A. chinensis, similar results were obtained except that SA and MJA did not affect disease development. Reduction in disease incidence and severity on A. deliciosa using ASM was correlated with a superoxide burst, the formation of necrotic spots and callose deposition, while on A. chinensis no superoxide burst or callose deposition was detected. Genes involved in plant–pathogen interactions were induced after treatment with ASM in A. deliciosa and, to a lesser extent, in A. chinensis. Those differences in gene expression and physiological responses after treatment with ASM are consistent with the different susceptibility to Psa observed between A. chinensis and A. deliciosa.